Fuzzing: Hack, Art, and Science. - GODEFROID, PATRICE (Communications of the ACM, 2020)
The article discusses the software security concept of fuzz testing, also known as fuzzing, and its significance in discovering computer security vulnerabilities. It also examines static program analyzers and manual code inspection.